Dieta y ejercicio. Control y regulación en los discursos de profesionales de las expresiones motrices (2016)
ABSTRACT: This article is a product from the research named, On Sun and Shade Memories. This is a recovery from the experience of The Motor expressions stages (2014 – 2015), performed with 20 graduates of the Institute of Physical Education of the University of Antioquia (Medellín – Colombia). Objective: The aim of one of the perspectives addressed in the study, was to characterize the body culture of those who practice physical education, sports, recreation and related areas in different stages, and specifically, this approach is to identify the motor expression professionals’ speech, the concerns about eating habits, dietetics and nutrition as mediators of health-body culture dimension- and to reveal individual’s regulatory potential. Materials and Methods: Based on reflexive ethnography, supported by interviews, visual records, observations and workshops implemented with motor expression professionals from the city of Medellín. Results: The study allowed us to understand the control function of guidance coming from dietetics and nutrition in two ways: teacher-student, the recurrence to the knowledge on the nutrition and dietetics fields, from the speech of motor expressions’ professionals and the complexity of compliance with what it should be, manifested in eating habits.